Лапы, крылья, три хвоста - Егорова Наталья (Астрель, 2007)
3-5 Экземпляры: (20240111) / Инвентарный номер: 32514 / Цена: 184.58 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Е 30 / ГРНТИ: 17 / ББК: 84(2=411.2)6